Spatial Analysis of Unemployment Level in Java Island in 2023 - Nuriya, Alvi Shafira Khoiri; Nihayah, Dyah Maya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Unemployment is one of the problem economy the largest in the world. In Indonesia, the number of unemployment reached 7.86 million people. Java Island is island with the highest Open Unemployment Rate (TPT) reaching 4.60 million people or equivalent with 58.52%. Areas with level unemployment highest located in the provinces of Banten, West Java and DKI Jakarta. This is become suspicion beginning existence regional influence so that need done analysis spatial. The method used in study This is analysis spatial with use Geographically Weighted Regression (GWR) method with a linear regression model, as well as method regression spatial for know factor determinant main. Data used originate from the Central Statistics Agency (BPS) and includes variable index development human, level participation work, level education, minimum wage and density residents in each province and district or cities in Java Island. Research results show that there is pattern unemployment that is clustered in several areas, especially in the areas urban with density high population and moderate industry experience change structural. The main factors that contribute to level unemployment is limited access to quality education and opportunities work that is not evenly distributed. Findings This can become runway for government in to design policy more employment effective and based territoriality for reduce unemployment in a way sustainable.